Bertholletia excelsa Humboldt & Bonpland (Lecythidaceae): morphological aspects of fruit, seed and seedling - Santos, João Ubiratan Moreira dos; Bastos, Maria de Nazaré do Carmo; Gurgel, Ely Simone Cajueiro; Carvalho, Ana Cristina Magalhães (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2006)
Bertholletia excelsa Humboldt & Bonpland is a tree that can reach up to 50m, known popularly as brazilian nut and castanha-do-pará, it happens in the whole Amazonian area; characteristic of the high forests, their nuts or seeds are very appreciated. Being known internationally, they constitute one of the main products of export of the Amazonian. It was aimed, at with this study, to describe the morphology of the fruit, of the seed and of the seedlings of the referred species; being used 30 fruits, 30 seeds and 10 seedlings. Enrolled the general morphology, the coloration, the texture, the consistence, the dehiscence and the indument of the fruits; of the seeds the tegument and the embryo, as well as the main vegetative elements of the seedlings. Was considered seedlings the development phase in that the first two eophylls were totally formed. The whole study was based in specialized literature and the main morphologic characters were illustrated with pictures. The studied species presents simple fruit, of the type poricidal capsule, in dehiscent, biseriate, opaque stalk, in brown tones, surface glabrous and fibrous; dark, opaque brown pericarp, crustacean, glabrous, slightly fibrous and septate; funiculus woody and in brown tones. Angular triangular seed axillary and estenospermic; tests clear brown, surface opaque, wrinkled and glabrous and of ligneous consistence; raphein tones chestnut tree darkness, rigid and salient, hilum oblong and in depression; embryo conferruminated. Gerrmination cryptocotylar hypogeous. Seedlings with simple eophylls, alternating, obovate, acute apex, margin serrate and brownish red, base symmetrical and attenuated, penniveined, broquidodromus and prevernal involute; hypocotyl is absent; epicotyl epigeous, orbicular, lenticeled, with many triangular cataphylls lanceolate and alternated.